Proposition of an Innovation Center in Santa Rosa, RS, Brazil, by means of the Via Cycle Methodology - Neves, Marta Silva; Escher, Lucas; Maristela Löff, Sandra; Duarte Ferreira, Juliana; Augusto Biz, Alexandre; Stefani Teixeira, Clarissa (International Journal for Innovation Education and Research, 2021)
A successful Innovation Center (IC) needs to be closely related to the territory in which it is inserted and have its functions aligned with regional development, the supply of facilities, services and resources and the promotion of culture and the innovation and entrepreneurship connection. This study aimed to develop stages of recognition and mapping of elements that underlie the implementation of an IC in the city of Santa Rosa, state of Rio Grande do Sul, Brazil, among them the challenges related to innovation faced in the city; the personas and actors involved; the identification of solutions; the potential stakeholders partners; the proposition of an action plan; and the presentation of this plan to those involved in the process. National and international ICs were analyzed as references for the study, the main ICs of Rio Grande do Sul, the state where Santa Rosa is located were mapped, and the innovation pathway of the city was addressed. Using the Via Cycle Methodology, the interactions between the actors and stakeholders that deal with innovation were studied, the challenges faced were identified, and a solution was proposed to face the perceived challenges. For this result, strategies capable of encompassing the various actors mapped and involved in the structuring pillars of the territory (education, governance, public power, and culture) were suggested, with the intention of proposing the implementation of the IC. The breakdown of these pillars into detailed actions resulted in a significant educational, social, cultural, and economic potential, whose details can serve as references to boost innovation-oriented experiences, meet technological needs, and strengthen various dimensions.